2021
DOI: 10.1007/s11356-021-14264-z
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the dynamic interactions between economic growth and environmental pollution in Italy: evidence from a gradient descent algorithm

Abstract: Although the literature on the relationship between economic growth and CO2 emissions is extensive, the use of machine learning (ML) tools remains seminal. In this paper, we assess this nexus for Italy using innovative algorithms, with yearly data for the 1960–2017 period. We develop three distinct models: the batch gradient descent (BGD), the stochastic gradient descent (SGD), and the multilayer perceptron (MLP). Despite the phase of low Italian economic growth, results reveal that CO2 emissions increased in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…Data science for social good (DSSG) and artificial intelligence for social good (AISG) are the applications of data science and/or artificial intelligence for improving social outcomes (Magazzino & Mele, 2022 ; Rostami-Tobar et al, 2021; Moore, 2019 ). DSSG core techniques include data science, data visualization, and quantitative models for a wide range of application areas, such as health, sustainability (Magazzino et al, 2021 ; Mele et al, 2021a , 2021b ), economic development (Mele et al, 2021a ), disaster relief operations, public safety, transportation (Magazzino et al, 2022 ), and human services. Catlett and Ghani ( 2015 ) launched a special issue to promote organizations collaborating with data scientists and applying data-driven quantitative tools for the social good.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Data science for social good (DSSG) and artificial intelligence for social good (AISG) are the applications of data science and/or artificial intelligence for improving social outcomes (Magazzino & Mele, 2022 ; Rostami-Tobar et al, 2021; Moore, 2019 ). DSSG core techniques include data science, data visualization, and quantitative models for a wide range of application areas, such as health, sustainability (Magazzino et al, 2021 ; Mele et al, 2021a , 2021b ), economic development (Mele et al, 2021a ), disaster relief operations, public safety, transportation (Magazzino et al, 2022 ), and human services. Catlett and Ghani ( 2015 ) launched a special issue to promote organizations collaborating with data scientists and applying data-driven quantitative tools for the social good.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Early studies introduced environmental pollution as an essential core variable in the health model ( 39 ). Further studies found that extensive economic development caused environmental pollution, especially air pollution, which directly caused much damage to human health ( 10 , 11 ). Diseases caused by environmental pollution mainly include respiratory conditions, heart diseases, etc., ( 40 , 41 ).…”
Section: Policy Background and Literature Reviewmentioning
confidence: 99%
“…e selection of trade partners according to their own development needs and the formulation of trade policies conducive to the country's development before engaging in international trade are of great importance to national economic development and political security [6]. Senturk et al explored the competitive relationship between oilimporting countries based on complex network theory and analyzed the evolution and transmission of oil trade competition patterns in conjunction with measures of competitive intensity [7].…”
Section: Related Workmentioning
confidence: 99%